Information System for Collecting Customer Collateral Using PHP and MySQL (Case Study BPR BKK, Giritontro, Wonogiri Branch): Sistem Informasi Pengambilan Agunan Nasabah Menggunakan PHP dan MySQL (Studi Kasus Bank Perkreditan Rakyat Badan Kredit Kecamatan Cabang Giritontro Wonogiri) - Laraswati, Andri; Purbiyanto , Eko; Naury, Chairullah (Politeknik Harapan Bangsa Surakarta, 2023)
Rural Credit Bank of Giritontro District (BPR BKK Giritontro) is a financial institution engaged in savings and loans in the Giritontro District of Wonogiri. BPR BKK's customers provide collateral when applying for loans, and once the loans are repaid, the collateral is returned. However, the current collateral retrieval process at BPR BKK Giritontro is done manually through recording in a logbook maintained by administrative staff, leading to issues such as vulnerable and easily lost storage media. Additionally, there can be delays in the retrieval process if the administrative staff is absent, as only they have access to the storage cabinet key. The logbook system also hinders data search efficiency for collateral retrieval verification. This research aims to develop an information system for customer collateral retrieval to assist the administrative department in managing collateral retrieval. The author adopts the System Development Life Cycle (SDLC) waterfall model for system development and utilizes PHP programming language and MySQL database for the information system implementation.